Peran Pengelolaan Keuangan Bagi UMKM di Kota Batam - Khadijah Khadijah; Neni Marlina Br Purba (Prosiding, 2020)
MSMEs are a major pillar of the Indonesian economy. MSMEs are expected to boost Indonesia's economy as a whole with various business opportunities from the economic crisis. One of the main and concrete challenges faced by MSME entrepreneurs is related to fund management. The main initiative in fund management is to practice accounting well. Accounting that is considered difficult turns out to be easy to understand and practice. The implementation of accounting is an easy step but provides tremendous benefits for MSMEs. financial management is an important thing that remains to be considered. Basic accounting science is a must-have if you want the business to run smoothly. The importance of accounting in the business of MSMEs can know the business conditions, help the loan process, manage business finance, etc. The descriptive method used by the sample is the owner of MSMEs in Batam City with samples in this study taken by 95 respondents. The results of the study according to 4 indicators researched from financial management show that the overall respondent understands the use of budgets, budgeting and forecasting future efforts. Then in terms of recording the entire respondent performs financial records only within the sales and purchase limits only. Reporting indicators no respondents do because the business is only a personal business and considers it unnecessary to do financial reporting. The last of the overall control indicators of respondents used control over the business by using a note.